An Evaluation Of The Indonesian Law And Policy On Small-Scale Fisheries - Ariadno, Melda Kamil; Amelina, Fitri (Journal of Sustainable Development Law and Policy, 2025)
Fisheries play an important role in food security, especially in Indonesia. Two-thirds of the land area is covered by sea and its coastal community is the largest one among the Indonesian communities. Data obtained from the Ministry of Fisheries and Marine Affairs in 2011 shows that 95 per cent of the operators in the Indonesian fisheries sub-sector operated on the small-scale and 42 per cent of them were women. Small-scale fisheries provide a great contribution to the food security of Indonesia and the world, either in the context of fulfilling animal protein needs or providing a basis for the local, national, and international-scale trade in fisheries products. The Indonesian fishing community contributes to the 90 per cent total amount of world fishers, of which half are women (FAO, 2012). To improve this small-scale fishing, the Food and Agriculture Organization (FAO) has initiated the adoption of ‘International Guidelines for Securing Sustainable Small-Scale Fisheries.’ It is still in negotiation regarding the main principles that are to be implemented by states in securing the sustainability of small-scale fisheries and figuring out the solutions that need to be taken by Indonesia to improve the living standard of the small-scale fisherman/woman. The article aims to provide problems identification, regulations assessment, and recommendations on small-scale fisheries in Indonesia.